Chlorogenic acid alleviates the intestinal barrier dysfunction and intestinal microbiota disorder induced by cisplatin - Tian, Ruiqi; Ding, Yinchuan; Zhang, Shijie; Li, Min; Wang, Yiran; Wu, Qi; Ding, Huanhuan; Song, Chengjie; Shi, Ce; Xue, Min (Frontiers in Microbiology, 2025)
IntroductionThe intestinal mucosal barrier is an important line of defense for the body, protecting it from intestinal bacteria, endotoxins, and antigens. Cisplatin, a clinical important chemotherapy medicine, is found the side effect with impairing intestinal epithelial cells’ structure and function, even causes intestinal mucositis which causes patients immense suffering and hinders the process of cancer treatment. Chlorogenic acid, as the component only second to caffeine in coffee, has been proved the contribution on cardiovascular and gastrointestinal benefits. So, we investigate the protective effect of chlorogenic acid on cisplatin induced intestinal barrier structure and function injury in mice from the perspective of gut microbiota.MethodsC57BL/6J mice were divided into 4 groups, including the control group, a cisplatin group, a chlorogenic acid treatment group receiving intraperitoneal injections alongside cisplatin (Cis + CGA1), and the last group pre-treated with chlorogenic acid before cisplatin administration (Cis + CGA2). The inflammation factor of IL-6, IL-1β, and TNF-α in colonic tissue and serum were detected, respectively. To explore the protection of chlorogenic acid on mucosal barrier’s integrity, we also detected the fecal LPS and the expression of occludin and ZO-1 proteins in colon tissue. And H&E staining was used to study the histopathological conditions of the colon tissue. Moreover, this article also utilized16S rDNA sequencing to analyze the gut microbiota of feces.ResultsChlorogenic acid administration reduced IL-6, IL-1β, and TNF-α level in both colon tissue and serum compared to the cisplatin alone treatment group. Furthermore, chlorogenic acid pretreatment notably improved intestinal barrier integrity by enhancing the expression of occludin and ZO-1 proteins in colon tissues. Moreover, 16S rDNA sequencing showed that compared with the control group, cisplatin group showed a reduced microbiota diversity, elevating abundance of Proteobacteria and pro-inflammatory environment of the increased Firmicutes/Bacteroidetes (F/B) ratio. However, chlorogenic acid treatment especially the pretreatment reversed the reduced microbiota diversity, elevating abundance of Proteobacteria and F/B ratio.DiscussionMicrobiota diversity and all results suggest that chlorogenic acid treatment was able to mitigate these intestinal microbiota disorder and diversity reduction induced by cisplatin, effectively offer a protective effect against the inflammatory response and destruction of the mucosal barrier in the intestines caused by cisplatin.